(untitled) (Medicine Today, 2020)
Introduction: Mental health problem is a major public health issue in the world across the developed and developing countries. However, data in most of the developing countries including Bangladesh are scarce. In Bangladesh, socio-political situation is insecure and unstable with poverty and vulnerable to natural disaster which causes psychiatric morbidity. The pattern of psychiatric morbidity attended in OPD is quite different from that in government hospital. This study was aimed to assess the diagnostic pattern of psychiatric morbidity among the attended patients in a out patient department in a medical college. Materials and Methods: The study was carried out in a OPD which is situated in 500 bedded private medical college in the sylhet city. All the information including longitudinal histories of patients was recorded in files and the diagnosis was confirmed by psychiatrist. All information notes were recorded in register. Socio -demographic parameters and family history of mental illness were collected from the record file of individual patient. Results: Among 304 patients 184 (60.53%) were males and 120 (36.47%) were females. More than 50% of patients were in the age group of 18 to 37 years. Most common psychiatric disorders were schizophrenia and other psychotic disorders (39.4%), mood disorder (18.75%), borderline personality disorder (3.6%), conduct disorder (2.3), somatoform disorder (1.6%), anxiety disorder (0.7%), organic psychiatric disorder (2%), impulse control disorder (1.3%) and adjustment disorder (0.7%). Conclusion: Major forms of psychiatric disorders are common both in urban and rural areas of Bangladesh. Medicine Today 2020 Vol.32(1): 52-54